2005
DOI: 10.1124/dmd.105.006544
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATION OF ALDEHYDE OXIDASE ACTIVITY IN VIVO FROM CONVERSION RATIO OF N1-METHYLNICOTINAMIDE TO PYRIDONES, AND INTRASPECIES VARIATION OF THE ENZYME ACTIVITY IN RATS

Abstract: ABSTRACT:The in vivo conversion ratio of N 1 -methylnicotinamide (NMN) to N 1 -methyl-2-pyridone-5-carboxamide (2-PY) and N 1 -methyl-4-pyridone-3-carboxamide (4-PY) as a parameter for the estimation of aldehyde oxidase level in rats was examined. NMN and its pyridones (2-PY and 4-PY) are usually detected in the urine of rats. When we measured the ratio of the amount of pyridones to the total amount of NMN and pyridones (RP value) in the urine of rats, marked intraspecies variations were observed. The variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
(26 reference statements)
0
21
0
Order By: Relevance
“…The enzyme in liver of various species catalyzes the oxidation of various aldehydes and nitrogenous heterocyclic xenobiotics, such as methotrexate and cyclophosphamide (Beedham, 1985;Kitamura et al, 2006), and also catalyzes the metabolism of physiological compounds, such as retinaldehyde (Huang and Ichikawa, 1994). However, there are marked species differences and strain differences of the enzyme activities for oxidative reaction in rats and mice (Beedham, 1985;Schofield et al, 2000;Kitamura et al, 2006;Sugihara et al, 2006). This has presented problems in preclinical studies.…”
mentioning
confidence: 97%
“…The enzyme in liver of various species catalyzes the oxidation of various aldehydes and nitrogenous heterocyclic xenobiotics, such as methotrexate and cyclophosphamide (Beedham, 1985;Kitamura et al, 2006), and also catalyzes the metabolism of physiological compounds, such as retinaldehyde (Huang and Ichikawa, 1994). However, there are marked species differences and strain differences of the enzyme activities for oxidative reaction in rats and mice (Beedham, 1985;Schofield et al, 2000;Kitamura et al, 2006;Sugihara et al, 2006). This has presented problems in preclinical studies.…”
mentioning
confidence: 97%
“…[11][12][13][14][15] We demonstrated that an obvious individual difference in AOX1 activity in Donryu strain rats is derived from a single nucleotide substitution of the AOX1 gene consisting of approximately 4300 base pairs. In addition, the mechanism of the individual difference is true to strain differences in rat.…”
mentioning
confidence: 99%
“…The expression and activity of AO in liver of h-PXB mice have been reported (Kitamura et al, 2008). In contrast, the AO activity of r-PXB mice seems to be low, probably because rat hepatocytes for r-PXB mice were derived from Crj:SD rats, which show lower AO activity than other strains of rats (Moriyasu et al, 2006;Sugihara et al, 2006;Itoh et al, 2007). The levels of expression P450 and non-P450 enzymes and metabolic activities in fresh h-hepatocytes are similar to dmd.aspetjournals.org those of actual human hepatocytes (Yoshitsugu et al, 2006;Yamasaki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%